PERAN INTERVENSI MINIMAL TIPE ABLASI RADIOFREKUENSI DALAM PENANGANAN NYERI KRONIK - Yusak Mangara Tua Siahaan,* Hugo Dwiputra Wiradarma** (Neurona Majalah Kedokteran Neuro Sains, 2018)
PAIN IS ONE OF THE MOST COMMON COMPLAINTS IN EVERYDAY CLINICAL PRACTICE THESE COMPLAINTS NOT ONLY CAUSE DISRUPTION TO PHYSICAL FUNCTIONING BUT ALSO TO SOCIAL MENTAL AND ECONOMIC FUNCTIONS RECENT STUDIES HAVE DEMONSTRATED THE POTENTIAL OF INTERVENTIONAL THERAPY INCLUDING RADIOFREQUENCY RF ABLATION IN THE MANAGEMENT OF CHRONIC PAIN